Practical Windows PowerShell scripting - Posey, Brien (LiveLessons (Indianapolis, Ind.), 2016)
"Learn from an expert while you become the expert. Practical Windows PowerShell Scripting LiveLessons begins with the basics of working with PowerShell and progresses to areas that are not typically covered, such as building GUI interfaces. The entire video is designed to be hands on, and is created by an instructor who is highly experienced with creating complex PowerShell scripts. The goal of this video series is to teach skills for building PowerShell scripts that serve a practical purpose. These scripts can be used in day-to-day tasks for most jobs. The videos assume no prior PowerShell knowledge. The information is presented in such a way that each lesson builds onto the previous lesson, working toward the eventual coverage of advanced PowerShell concepts."--Resource description page.